Search translations for a Scoping review on published literature on PFAS measures and Kidney Outcomes - Reis, Heidi (My University, 2026)
This is the full search strategy developed by librarian Heidi Reis in consult with Dr. Suzanne Lea, Dr. Qiao Wang and Molly Stanly for a scoping review on published literature on PFAS measures and kidney outcomes. The search was performed on 3/12/2025 in Medline (PubMed), embase (embase.com), scopus (elsevier), Agricultural and Environmental Science Collection (ProQuest).
Keywords: PFAS; kidney disease; evidence synthesis